2017
DOI: 10.1161/jaha.116.005449
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilities to Health Disparities and Statin Use in the REGARDS (Reasons for Geographic and Racial Differences in Stroke) Study

Abstract: BackgroundStatins may be underutilized in certain vulnerable populations, but the effect of cumulative vulnerabilities within 1 individual is not well described. We sought to determine the likelihood of receiving statins with an increasing number of vulnerabilities in an individual, after controlling for factors known to influence health services utilization.Methods and ResultsWe identified 18 216 participants from the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study who had a statin ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 22 publications
(37 reference statements)
1
58
1
Order By: Relevance
“…166 With this observation, statins (hydroxymethylglutaryl-coenzyme A reductase inhibitors) and other lipid lowering drugs have been widely used for clinical studies, which have reported a decrease in AAA expansion rates. 57,81,145 Yet, the effect of statins has been ambivalent for most AAA cases, 48,82,149 and there is an undetermined possibility of cancer development 179 and adverse musculoskeletal and connective tissue disorders with statin use. 58 Doxycycline is one of the most studied drugs in AAA preclinical models 52 with the potential to inhibit MMP-2 and −9 174 and decrease AAA growth.…”
Section: Pgg As a Potential Therapeutic Option For Aaa Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…166 With this observation, statins (hydroxymethylglutaryl-coenzyme A reductase inhibitors) and other lipid lowering drugs have been widely used for clinical studies, which have reported a decrease in AAA expansion rates. 57,81,145 Yet, the effect of statins has been ambivalent for most AAA cases, 48,82,149 and there is an undetermined possibility of cancer development 179 and adverse musculoskeletal and connective tissue disorders with statin use. 58 Doxycycline is one of the most studied drugs in AAA preclinical models 52 with the potential to inhibit MMP-2 and −9 174 and decrease AAA growth.…”
Section: Pgg As a Potential Therapeutic Option For Aaa Patientsmentioning
confidence: 99%
“…(c) Thirugnanasambandam et al . 149 utilized a similar rat calcium chloride model and utilized PGG to suppress aneurysm growth. As shown, PGG treatment was also able to suppress MMP influx to the aorta, which led to a reduction of inflammation.…”
Section: Figurementioning
confidence: 99%
“…female sex and black race, or uninsured and black race) predicted an even lower rate of statin use compared to groups. 10 These socioeconomic barriers preclude appropriate secondary medical management for stroke in this population.…”
Section: Introductionmentioning
confidence: 99%
“…5 Differences in genetic traits, poor glycemic control, a high incidence of obesity, and the presence of insulin resistance contribute to this increased risk, which may be linked to racial disparities in health care. 14 Lower rates of statin use by AA/B vs W patients have been demonstrated in primary care populations, 15,16 reaffirming the disparities in the treatment of CVD, which is the first and second leading cause of death in AA/B and H/L patients, respectively. 17 In a retrospective study that used the 2015 Patient and Provider Assessment of Lipid Management registry data, AA/B patients were less likely than W to be treated with a statin (70.6% vs 74.8%, respectively; P 5 .02).…”
Section: Discussionmentioning
confidence: 89%